Single‐Photon Emission: Bright Room‐Temperature Single‐Photon Emission from Defects in Gallium Nitride (Adv. Mater. 12/2017). Issue 11 (22nd March 2017) - Berhane, Amanuel M.; Jeong, Kwang‐Yong; Bodrog, Zoltán; Fiedler, Saskia; Schröder, Tim; Triviño, Noelia Vico; Palacios, Tomás; Gali, Adam; Toth, Milos; Englund, Dirk; Aharonovich, Igor
Abstract : The cover depicts an image of bright single photons emitted from gallium nitride. This illustrates a potential quantum nanoelectronic circuit that uses single photons for information transfer, as described in article number 1605092 by Dirk Englund and Igor Aharonovich.